2021
DOI: 10.1111/aphw.12292
|View full text |Cite
|
Sign up to set email alerts
|

Field observations and survey evidence to assess predictors of mask wearing across different outdoor activities in an Argentine city during the COVID‐19 pandemic

Abstract: We here studied some potential factors underlying variation in compliance with preventive behaviors against COVID‐19 by studying mask wearing during outdoor recreational activities in a midsize city of Argentina in 2020. The originality of present research relies on the complementation of observational (N = 15,507) and survey (N = 578) data and in assessing the determinants of and disposition to the same preventive behavior across activities. In Study 1, we did 8 weeks of unobtrusive systematic observation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 40 publications
(55 reference statements)
2
9
0
Order By: Relevance
“…Already decreasing during the third orange code teaching period, the lower compliance with contactless greetings could reflect a lesser attention paid by students to comply with barrier gestures beyond any controlled by dedicated persons. Such a decline of compliance with mask wearing over time was reported previously [ 19 ]. In the present situation, the acceleration of vaccination deployment in the population (19.3% of Walloon adults were fully vaccinated by 24 May 2021 vs. 40.6% by of 21 June 2021 [ 26 ]) and the decrease in the number of new cases each week (from 4585 in week 21 to 615 in week 25 vs. 9742 in week 11 in Wallonia [ 27 ]) may have induced a lower risk perception.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Already decreasing during the third orange code teaching period, the lower compliance with contactless greetings could reflect a lesser attention paid by students to comply with barrier gestures beyond any controlled by dedicated persons. Such a decline of compliance with mask wearing over time was reported previously [ 19 ]. In the present situation, the acceleration of vaccination deployment in the population (19.3% of Walloon adults were fully vaccinated by 24 May 2021 vs. 40.6% by of 21 June 2021 [ 26 ]) and the decrease in the number of new cases each week (from 4585 in week 21 to 615 in week 25 vs. 9742 in week 11 in Wallonia [ 27 ]) may have induced a lower risk perception.…”
Section: Discussionsupporting
confidence: 79%
“…In the present situation, the acceleration of vaccination deployment in the population (19.3% of Walloon adults were fully vaccinated by 24 May 2021 vs. 40.6% by of 21 June 2021 [ 26 ]) and the decrease in the number of new cases each week (from 4585 in week 21 to 615 in week 25 vs. 9742 in week 11 in Wallonia [ 27 ]) may have induced a lower risk perception. As highlighted in previous studies [ 10 , 11 , 19 ], a lower risk perception was associated with a lower compliance with barrier gestures and could, therefore, explain a relaxation of their implementation. That said, this hypothesis should be confirmed, as a study realized in 10 universities around the world [ 28 ] showed that compliance with barrier gestures was not uniformly influenced by the same factors, given the underlying differences between hygiene measures and measures related to physical distancing.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Alternatively, it may be that the phrasing of the items (asking for instance how frequently a behaviour was avoided, rather than engaged in) could have affected reported frequencies and thus the validity of the results. Varying compliance with different types of measures has also been established in the Argentinian context [50], with divergent factors predicting engagement in different measures. Overall, there will be a need to better understand and address intersecting vulnerabilities (race, gender, poverty [reflected for instance in high population density, large households, communal water sources], and geopolitics) in sub-Saharan Africa contexts [48,51,52] to increase rates of compliance with protective measures in future pandemics.…”
Section: Discussionmentioning
confidence: 99%
“…Third, and more narrowly, we contribute to the literature on the social determinants of face mask wearing. The existing papers in this literature rely either on vignette-based experiments and surveys (Bokemper et al, 2021;Barceló and Sheen, 2020;Rudert and Janke, 2021;Goldberg et al, 2020;Barile et al, 2021) or instead observational data (Freidin et al, 2022;Woodcock and Schultz, 2021). We contribute to this literature by conducting the first ever randomised field experiment on the social determinants of face mask use.…”
Section: Introductionmentioning
confidence: 99%